Report of Meeting. The Fourth Debrecen-Katowice Winter Seminar on Functional Equations and Inequalities February 4-7, 2004 Matráháza, Hangary - AMSil, Redakcja (Annales Mathematicae Silesianae, 2004)
Report of Meeting. The Fourth Debrecen-Katowice Winter Seminar on Functional Equations and Inequalities February 4-7, 2004 Matráháza, Hangary.